Small holders managed manure nutrient losses and their implications on environment - Alemayehu, N.; Masafu, M.M.; Ebro, A.; Tegegne, Azage (Horizon Research Publishing Co., Ltd., 2015)
Animal manure is rich in absorbable plant nutrients and an appropriate addition of manure into the soil respond to high crop productivity than use of commercial fertilizer. But volatilization of ammonia due to high temperature and leaching of nitrate, phosphorous and potassium into the soil due to rainfall results in the loss of manure nutrients. The objective of this study was to assess manure nutrient loss and gaseous emissions due to inappropriate manure management. The study was conducted in central Ethiopian highland, east of the capital Addis Ababa. The study included laboratory analysis for manure nutrients contents from sampled units and the manure management type was captured through focus group discussions. Storage age has impacted on nutrient losses as a result the highest loss of N, P and K occurred in 2 to 3 years at the rate of 84%, 19% and 42% , respectively. The analysis of variance showed that at P<0.05, there was a significant difference in storage age for N and K, but there was no significant difference for P across different storage ages. Shade type and manure heap height has no significant impact on nutrient losses. The total carbon equivalent (CO2e) gas emitted per household per annum was estimated at 11, 276 kg CO2e (i.e. 8 200 kg CO2e came from methane directly released by livestock plus their manure, 2 694 CO2e came from N2O emissions from manure management and 381.48 kg CO2e came from CO2 released from manure burning) that is about 2 tons CO2e per capita per year, twice the value reported for Ethiopia emission in 2005. The largest emissions were from methane (72.6%), nitrous oxide (24%) and carbon (3.4%), this result appeal for a need to improve livestock and manure management systems under smallholders' agriculture in order to curb the challenges of global carbon release.